MENUNGGU NASIB RUU PENYANDANG DISABILITAS DI DPR - , Agus Rianto (Fakultas Hukum Universitas Sebelas Maret, 2015)
AbstractThe Persons with Disabilities in this country are so excited to welcome the bill on Disability which is intended to replace Law No. 4 of 1997 on Persons with Disabilities that are not in accordance with the demands of time, but they were disappointed because the government as if forgetting the Bill, so far about the Disability Bill has not passed into law official. Because of this the Federation of Indonesian Welfare of Persons with Disability (FKPCTI) held an activity entitled